Evaluasi Penerapan Sistem Akuntansi Penggajian Karyawan Dalam Mendukung Efektifitas Pengendalian Internal (Studi Kasus Pada PT Sutrajaya Indahtama Tanggulangin Sidoarjo) - Yanira Cahya Sari; Sigit Puji Winarko (POLITEKNIK CAHAYA SURYA, 2020)
This research has a background on the importance of implementing a good payroll accounting system in a company. Because payroll is a routine expenditure and a considerable expenditure by the company. The objectives in this research are (1) To determine the implementation of employee payroll accounting information system at PT Sutrajaya Indahtama Tanggulangin Sidoarjo (2) To evaluate the implementation of payroll accounting information systems at PT Sutrajaya Indahtama Tanggulangin Sidoarjo, it can support internal control. This research uses a qualitative approach by descriptive methods. Data sources used are primary and secondary data. The procedure of collecting data in this research was using observation, interview, and documentation. The result of this research indicates that the implementation of the payroll accounting system in supporting the effectiveness of internal control at PT Sutrajaya Indahtama is good, but there are still multiple task among the personnel function, time recording function, salary register function, and accounting functions that performed by one function, namely the personnel function.Keyword: Payroll Accounting System, Internal Control